Proton Beam Therapy in Pediatrics : A Review - Nuramalia, Putri Pradita; El Jannah, Syarifah Miftahul (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2024)
Pediatric cancer, including leukemia and brain tumors, is increasingly diagnosed, with about 400,000 cases annually. Conventional radiation therapy, while effective, can lead to long-term side effects, including secondary cancers. This review paper aims at discussing what proton beam therapy (PBT) has to offer for children suffering from cancer looking at its advantages and disadvantages. Literature on PBT and conventional radiotherapy was reviewed to compare treatment efficacy and side effects. PBT allows precise tumor targeting while minimizing damage to surrounding healthy tissue, resulting in fewer long-term effects. Studies show higher conformity indexes for PBT, reducing risks of growth disorders and cognitive impairment. Proton beam therapy shows significant promise for improving pediatric cancer treatment outcomes and quality of life. However, high costs and limited long-term data hinder its broader adoption, necessitating further research to optimize its use.